Formation of 1, 3‐Diphosphacyclobutadiene Complexes from Phosphaalkynes and Their Coordination Behavior. Issue 10 (April 2014) - Rummel, Eva‐Maria; Eckhardt, Maria; Bodensteiner, Michael; Peresypkina, Eugenia V.; Kremer, Werner; Gröger, Christian; Scheer, Manfred
Abstract: Invited for the cover of this issue is the group of Manfred Scheer at the University of Regensburg. The cover image shows organometallic and inorganic building blocks being combined to form unprecedented new species. Abstract : Most conventional polymers cannot be broken into monomers at room temperature without using special reagents. In the present case this feat becomes possible... Read more about the story behind the cover in the Cover Profile and about the research itself onp. 1625 ff .